“EKSISTENSI DAN PENERAPAN PIDANA PEMECATAN DARI DINAS MILITER SEBAGAI PIDANA TAMBAHAN DALAM PERSPEKTIF HUKUM PIDANA KHUSUS - Faizal Akbar Sutarto (Badan Penerbit STIEPARI Press, 2022)
The additional sentence of dismissal from military service by the judge against the defendant based on the Military Court Decision Number 217 K/MIL/2019 shows the existence of other criminal systems outside the provisions regulated by the Criminal Code which are aimed at certain legal subjects that have special characteristics in criminal law or it can be said as special criminal law. The purpose of conducting this research is to find out the existence and application of the punishment for dismissal from military service as an additional punishment in the perspective of special criminal law. This research is normative juridical research or doctrinal research using statutory and judicial case approaches. The existence of the crime of dismissal from military service as an additional punishment in the perspective of special criminal law is a form of deviation from general criminal law originating from the Criminal Code as a source of material criminal law outside the Criminal Code, namely the Criminal Code. The application of the punishment for dismissal from military service as an additional additional punishment against the military in the perspective of special criminal law is applied based on the provisions of Article 26 of the Criminal Procedure Code and is applied based on the provisions of Article 2 of the Criminal Procedure Code and Law Number 48 of 2009 concerning Judicial Power